2017
DOI: 10.1167/iovs.17-22156
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Neuroglial Changes in the Superficial and Deep Nonperfused Areas on Optical Coherence Tomography Angiography

Abstract: Systematic evaluation of the OCTA-OCT association showed structural changes in the neuroglial tissues corresponding to the lamellar NPAs and suggested the feasibility of layer-by-layer evaluation of the capillary nonperfusion in DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…Several studies also suggest that OCTA parameter alterations in the deep vascular layer are affected more severely than in the superficial vascular layer in NPDR [10, 11, 14-16, 17, 21, 23, 26]. OCTA parameters at the deep vascular layer were most significantly affected in patients with DME [4, 29-32]. …”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also suggest that OCTA parameter alterations in the deep vascular layer are affected more severely than in the superficial vascular layer in NPDR [10, 11, 14-16, 17, 21, 23, 26]. OCTA parameters at the deep vascular layer were most significantly affected in patients with DME [4, 29-32]. …”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Significant FAZ enlargement and vessel density decrease was also detected in patients with DME in the deep vascular layer compared to patients without DME [30, 31]. Nonperfusion area in the deep vascular layer was significantly correlated with cystoid spaces in patients with DME [32]. …”
Section: Octa Parameters In the Superficial Deep And/or Intermediatmentioning
confidence: 99%
“…But our results need more sample size to con rm. OCTA parameter alterations in the deep vascular layer are more serious than in the super cial vascular layer in NPDR [20][21][22][23], especially in patients with DME [24][25][26]. Our results showed that deep retinal VD in macular area was negatively correlated with FBG level, while VD in the super cial layer of the retina is not correlated, suggesting that deep retinal VD was more closely related to the change of blood glucose.…”
Section: Discussionmentioning
confidence: 67%
“…Capillaries in both layers were dropped out in most NPAs of the macular and extramacular areas, whereas we sometimes saw the lamellar nonperfusion in either the superficial or deep layer. 7 Since the vertical vessels connect between the capillaries in the superficial and deep layers, the NPAs in these layers might extend simultaneously. 19,20,[25][26][27] Another explanation might be that columnar neurovascular units are degenerated and concomitantly both capillary layers are dropped out.…”
Section: Discussionmentioning
confidence: 99%
“…4 Comparative studies between angiographic modalities and structural optical coherence tomography (OCT) have revealed the disorganized lamellar structure of inner layers in the nonperfused areas (NPAs). [5][6][7] Despite its clinical relevance, the mechanisms underlying retinal nonperfusion remain poorly understood in DR.…”
mentioning
confidence: 99%